La géographie mondiale, le congrès de Stockholm et le Canada - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1960)
The history of international geographical congresses can be divided in three periods, from 1871 to 1914, from 1922 to 1939, and since 1946. The most recent congress, which took place in Stockholm in 1960, was one of the most important ever beld.About 700 papers were presented at Stockholm, either in the Sections or in the Official Commissions. The most numerous papers were those dealing with human geography, economic geography, geomorphology, hydrography, periglacial geo-morphology and the teaching of geography. Of these 700 papers, only 15 were read by Canadian geographers, against 154 by American and 98 by Russian geographers.Still, this was the most important participation by Canadian geographers in any international geographical meeting ; however even if there bas been a marked progress since Canada's first participation at Venice in 1881, this is still not sufficient for a country with an international vocation like Canada. The main steps to take to improve the situation would be more, and especially more geographic, research, the preparation of special issues of Canadian geographical periodicals for every congress and the holding of an international geographical congress in Canada in 1968 or in 1972.